Evaluation of performance of human immunodeficiency virus antigen/antibody combination assays in Taiwan - Chun-Kai Chang; Cheng-Feng Kao; Pi-Han Lin; Hui-Lin Huang; Shu-Yuan Ho; Kuo-Chen Wong; Bo-Chang Lin; Chang-Ching Yeh; Chia-Yeh Lee; Chuan-Liang Kao; Chun-Nan Lee; Sui-Yuan Chang; et al. (Journal of Microbiology, Immunology and Infection, 2017)
Background: The fourth-generation human immunodeficiency virus (HIV) combination assay, which can simultaneously detect the presence of anti-HIV antibody and HIV antigen, has been shown to shorten the window period in HIV diagnosis compared with the third-generation HIV antibody immunoassay. This study was aimed to determine the performance of HIV combination assays in Taiwan, where the HIV-1 seroprevalence is 0.007% and HIV-2 infection has never been reported. Methods: Performance of three fourth-generation HIV Ag/Ab combination assays (Dia.Pro, Wantai, and Bio-Rad) and one third-generation HIV Ab immunoassay (AxSYM HIV 1/2 gO) was assessed. Results: A total of 152 specimens, including 86 confirmed HIV-seropositive and 66 HIV-seronegative samples, were used in the study. The sensitivity of four assays varied from 98.8% to 100%, and specificity varied from 98.5% to 100%. Performance of the 75 equivocal samples, the HIV status of which was confirmed later, in terms of negative prediction varied from 81.8% to 87.5%. The Bio-Rad and Dia.Pro assays exhibited higher sensitivity for the detection of p24 antigen among the three fourth-generation HIV combination assays. Conclusion: The three fourth-generation HIV Ag/Ab combination assays exhibited better sensitivity, specificity, and negative prediction than the third-generation HIV Ab immunoassay.